TRAINING AND RETRAINING AS A TOOL FOR PROMOTING WORKERS’ PRODUCTIVITY IN NIGERIA - Oyitso, Mabel; Olomukoro, C. O. (Sokoto Educational Review, 2015)
Human resources are the key element in any organization as they plan, coordinate, organize and harness all other resources towards the achievement of organizational goals. For any organization to increase its productivity level depends on the level of competence of its workforce. Hence, the need for training and retraining of workers to develop their abilities in order to function effectively and efficiently in the organization. Training is an indispensable tool for human and national development, hence a worthwhile investment for greater productivity in the organization. Training can be viewed as the acquisition of skills, knowledge and abilities to enable one function effectively in the performance of one’s job. The major types of training for workers are in-service training made up of on – the – job and off – the – job training. Training makes workers to be confident, enriches employee’s knowledge and increased performance skill, creates greater efficiency and effectiveness, increases productivity and leads to higher profitability. The major problems affecting the training of workers are inadequate finance and lack of constant training. Therefore, periodic training should be organized for workers to keep them abreast of technological changes in their work and adequate financial allocation should be devoted to training of workers in the organization.